Development and validation of combined symptom‐medication scores for allergic rhinitis. Issue 7 (15th January 2022) - Sousa‐Pinto, Bernardo; Azevedo, Luís Filipe; Jutel, Marek; Agache, Ioana; Canonica, G. Walter; Czarlewski, Wienczyslawa; Papadopoulos, Nikolaos G.; Bergmann, Karl‐Christian; Devillier, Philippe; Laune, Daniel; Klimek, Ludger; Anto, Aram; et al.
Abstract: Background: Validated combined symptom‐medication scores (CSMSs) are needed to investigate the effects of allergic rhinitis treatments. This study aimed to use real‐life data from the MASK‐air ® app to generate and validate hypothesis‐ and data‐driven CSMSs. Methods: We used MASK‐air ® data to assess the concurrent validity, test‐retest reliability and responsiveness of one hypothesis‐driven CSMS (modified CSMS: mCSMS), one mixed hypothesis‐ and data‐driven score (mixed score), and several data‐driven CSMSs. The latter were generated with MASK‐air ® data following cluster analysis and regression models or factor analysis. These CSMSs were compared with scales measuring (i) the impact of rhinitis on work productivity (visual analogue scale [VAS] of work of MASK‐air ®, and Work Productivity and Activity Impairment: Allergy Specific [WPAI‐AS]), (ii) quality‐of‐life (EQ‐5D VAS) and (iii) control of allergic diseases (Control of Allergic Rhinitis and Asthma Test [CARAT]). Results: We assessed 317, 176 days of MASK‐air ® use from 17, 780 users aged 16‐90 years, in 25 countries. The mCSMS and the factor analyses‐based CSMSs displayed poorer validity and responsiveness compared to the remaining CSMSs. The latter displayed moderate‐to‐strong correlations with the tested comparators, high test‐retest reliability and moderate‐to‐large responsiveness. Among data‐driven CSMSs, a better performance was observed for cluster analyses‐based CSMSs. High accuracy (capacity of discriminating different levels of rhinitis control) was observed for the latter (AUC‐ROC = 0.904) and for the mixed CSMS (AUC‐ROC = 0.820). Conclusion: The mixed CSMS and the cluster‐based CSMSs presented medium‐high validity, reliability and accuracy, rendering them as candidates for primary endpoints in future rhinitis trials. Abstract : This study assessed 317, 176 days of MASK‐air ® (Mobile Airways Sentinel NetworK) use from 17, 780 users aged 16‐90 years, in 25 countries. Real‐world data obtained with the MASK‐air ® app were used to develop combined symptom‐medication scores to assess the daily control of allergic rhinitis. These scores had medium‐high validity, reliability and accuracy, rendering them as candidates for clinical practice, and for primary endpoints in future rhinitis trials and observational studies.